Analysis of The Influence of Financial Information Systems, Internal Control Systems, and Information Technology on Quality of Financial Reports - Edhie Rachmad, Yoesoep; Ady Bakri, Asri; Irdiana, Sukma; Waromi, Juliana; Jansen Sinlae, Alfry Aristo (SEULANGA SYSTEM PUBLISHER, 2024)
The present study investigates the effects of information technology utilization, regional financial management information system implementation, and internal control system implementation on the integrity of financial reports generated by regional governments. A causal connection distinguishes the present investigation. Surveys were utilized to collect data, and questionnaires were distributed to respondents as part of the methodology. Respondents to the study were government employees. The samples used in this study were selected through convenience sampling. The research approach employed in this investigation was multiple regression analysis. According to this research, no observable correlation between local governments' degree of information technology implementation and the caliber of financial reports they generate can be identified. Nevertheless, the integrity of financial reporting can be improved through the implementation of financial management information systems and internal controls. An effective financial management information system can facilitate the production of financial reports of superior quality that adhere to specific regulations. The above system should address data security issues, timely information retrieval, report precision, report variety, and compliance with governmental financial report standards. Similarly, the enhancement of financial report quality generated by local governments can be achieved by implementing a resilient internal control system comprising communication, monitoring, the control environment, risk assessment, and control measures. The concurrent implementation of internal control systems, information technology implementation, and financial management information system establishment all contribute to improving the quality of financial reports produced by local governments.